Activity of Kelakai Leaf Extract (Stenochlaena palustris) as an Antioxidant and Antidiabetic: an in vitro and in silico study: Aktivitas Esktrak Daun Kelakai (Stenochlaena palustris) Sebagai Antioksidan dan Antidiabetes: Studi In Vitro dan In Silico - Nisa Kartika Komara; Hanasia Hanasia; Oktaviani Naulita Turnip; Farah Fauziyah Radhiyatulqalbi Ahmad; Muhammad Irmawan; Ysrafil Ysrafil; Angeline Novia Toemon; Muhammad Alif Sayyidinoor (Universitas Tadulako, 2026)
Background: Indonesia is the only country in Southeast Asia with the highest number of diabetics worldwide. In 2021, diabetes in Indonesia reached 10.6%, and it is predicted that this number will continue to increase, reaching 578 million by 2030 and 700 million by 2045. The way to overcome diabetes mellitus is by using drugs that can increase antioxidants and inhibit the activity of Î±-glucosidase; however, this method can have side effects, particularly on the digestive tract. Therefore, another alternative treatment is needed to reduce blood glucose levels in patients with diabetes mellitus, which is achieved by using natural ingredients. One of the natural ingredients predicted to have antioxidant and antidiabetic activity is kelakai leaves (Stenochlaena palustris). Methods: The content of your abstract must include background, aims of the study, used method, brief result and conclusion. Results: In this study, kelakai leaf extract showed potential as a source of bioactive compounds, particularly in terms of antioxidant activity and potential inhibition of Î±-glucosidase. This is indicated by the very strong IC50 value of 9,384 ppm. The best results were found in the nictoflorin compound, with a bond energy value almost close to the native ligand value (-7.7 kcal/mol) and interacting with the same amino acids as Î±-glucosidase, including Asp 542, Phe 575, Tyr 299, Trp 406, His 600, and Met 444. Conclusions: The potential of kelakai leaf extract as an antidiabetic is indicated by the interaction between Î±-glucosidase and all test compounds, as seen from the bond energy reflecting the level of affinity.